PEREMPUAN BURUK RUPA DI DALAM SASTRA - Wahyu Heriyadi (TELAGA BAHASA, 2019)
AbstractThe concept of beauty written by the authors of Indonesian contemporary women at this time can be said to experience significant changes, these changes can also be said to be a resistance effort in literature that presents the ugly concept of female characters written by female authors. Ugly is no longer a weak phase, but it is increasingly becoming a force and even power that is presented through the ugly main character. Through literature research on contemporary Indonesian women's novels and short stories, namely Saman's novel by Ayu Utami, the short story of Mereka Bilang, Saya Monyet! The work of Djenar Maesa Ayu, the Wanita Berwajah Penyok by Ratih Kumala, and Si Manis dan Lelaki Ke Tujuh by Intan Paramaditha. The result obtained is that even though the ugly woman has been defeated but at the same time she must be presented in a literary text, or give symbolic resistance through the character of a bad female character apparently towards the establishment of a beauty ideology and patriarchy.Key words: Female, Ugly, Short Story, Novel AbstrakKonsep kecantikan yang ditulis oleh pengarang perempuan kontemporer Indonesia pada saat ini dapat dikatakan mengalami perubahan yang signifikan, perubahan tersebut juga dapat dikatakan sebuah upaya perlawanan di dalam sastra yang menghadirkan konsep buruk rupa pada tokoh perempuan yang ditulis oleh pengarang perempuan. Buruk supa bukan lagi sebagai suatu fase yang lemah, tetapi semakin hadir menjadi sebuah kekuatan bahkan kekuasaan yang dihadirkan melalui tokoh utamanya yang buruk rupa tersebut.Melalui penelitian pustaka pada novel dan cerpen karya perempuan Indonesia kontemporer yaitu Novel Saman karya Ayu Utami, cerpen Mereka Bilang, Saya Monyet! Karya Djenar Maesa Ayu, Wanita Berwajah Penyok karya Ratih Kumala, dan Si Manis dan Lelaki Ke Tujuh karya Intan Paramaditha. Hasil yang didapatkan adalah meskipun perempuan buruk rupa telah dikalahkan namun sekaligus ia harus dihadirkan dalam teks sastra, atau memberikan perlawanan yang simbolis melalui karakter tokoh perempuan buruk rupanya terhadap kemapanan ideologi kecantikan dan patriarki.Kata-kata kunci: Perempuan, Buruk Rupa, Cerpen, Novel